Intercultural translation and the ecology of legal knowledges in the experience of Cherán, Mexico: elements for a new critical and militant legal practice. Issue 1 (2nd January 2020) - Andrade, Orlando Aragón
ABSTRACT: This article discusses the possibility of rethinking militant legal practices from the perspective of an ecology of legal knowledges. Based on experience of more than six years of militant work with the Purepecha community of Cherán, Mexico, I show how a legal practice was constructed to defend subaltern and social movement sectors from hegemonic groups. In doing so, I argue it also shifted critical potential to the very core of the production of legal practices itself. Drawing from empirical data from several interventions in two distinct fields, the judicial and the legislative, I discuss the site of a militant legal practice established from the logics of a horizontal epistemology, different from what I call the practices of the 'Lawyer King, ' and reflect on its potentials and limitations.